«Un coltello nella schiena del mondo». Lucio Dalla, la crisi della forma canzone e testi «intoccabili» di Roberto Roversi - Tomatis, Jacopo (L’ospite ingrato, 2024)
The collaboration between Roversi and Dalla – which includes the songs collected in Il giorno aveva cinque teste (1973), Anidride solforosa (1975) and Automobili (1976), as well as some unpublished material – is a one-of-a-kind in the history of the relationship between popular music and poetry in Italy: for the number of songs they co-authored, for the continuity of the relationship between the two and for the modalities of the collaboration itself. Roversi approached the song form as a self-taught experimenter, ignoring the conventions of the lyricist’s work. Dalla, for his part, treated the lyrics provided to him by the poet as “untouchable,” developing original strategies for setting them to music, in the context of a period of great innovation in international popular music and a general crisis of the song-form.